2001
DOI: 10.1021/jf000574n
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of Possible Role of Dietary Fiber in Lowering Postprandial Serum Glucose

Abstract: There have been many reports concerning the role of dietary fiber in lowering postprandial serum glucose, and the main mechanism was regarded as the viscosity of different dietary fibers in hampering diffusion of glucose and postponing absorption and digestion of carbohydrates. In this paper, two kinds of water-insoluble dietary fibers, water-insoluble dietary fiber of wheat bran and enzyme-resistant starch of maize amylose, and four kinds of water-soluble dietary fibers, water-soluble dietary fiber of wheat b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
341
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(358 citation statements)
references
References 11 publications
12
341
1
4
Order By: Relevance
“…The results suggested that the part of the antihyperglycemic actions of ginger may be by decreasing glucose absorption in vivo. The main mechanism concerning the role of dietary fiber in lowering postprandial serum glucose is the viscosity of different dietary fibers in hampering diffusion of glucose and postponing absorption and digestion of carbohydrates as these bind glucose and resultantly decrease the concentration of available glucose in the small intestine (Ou et al, 2001). Gallagher et al (2003) studied the ability of different plants to inhibit glucose diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that the part of the antihyperglycemic actions of ginger may be by decreasing glucose absorption in vivo. The main mechanism concerning the role of dietary fiber in lowering postprandial serum glucose is the viscosity of different dietary fibers in hampering diffusion of glucose and postponing absorption and digestion of carbohydrates as these bind glucose and resultantly decrease the concentration of available glucose in the small intestine (Ou et al, 2001). Gallagher et al (2003) studied the ability of different plants to inhibit glucose diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose adsorption capacity and amylase activity inhibition rate Glucose adsorption capacity and amylase activity inhibition rate were determined by the methods given by Ou et al (2001). The glucose content of the supernatant was determined using glucose assay kit (Coral, Tulip group, India).…”
Section: Functional Propertiesmentioning
confidence: 99%
“…Glucose diffusion and GDRI were determined according to the method of Ou et al (2001) with slight modifications. The fiber sample weighing 0.5 g was mixed with 25 mL of 50 mmol/L glucose solution.…”
Section: Glucose Diffusion Rate and Glucose Diffusion Reduction Indexmentioning
confidence: 99%
“…Trapping the glucose inside the gel may leach out slowly and prevent the sudden rise of the bloodglucose level. The viscous and gel-forming properties of soluble dietary fiber prevent macronutrient absorption, reduce postprandial glucose response and beneficially affect certain blood lipids (39). It is claimed that oral glucose tolerance in normal, type 1 or type 2 diabetic rats could be remarkably improved by administration of soluble dietary fiber (SDF) fraction.…”
Section: Health and Therapeutic Benefits Of Fenugreek Seedmentioning
confidence: 99%